Supplementary feeding and endangered avian scavengers: benefits, caveats, and controversies. Issue 4 (May 2016) - Cortés‐Avizanda, Ainara; Blanco, Guillermo; DeVault, Travis L; Markandya, Anil; Virani, Munir Z; Brandt, Joseph; Donázar, José A
Abstract : Large avian scavengers are among the most vulnerable vertebrates, and many of their populations have declined severely in recent decades. To help mitigate this marked reduction in abundance, supplementary feeding stations (SFS; colloquially termed "vulture restaurants") have been created worldwide, often without consideration of the scientific evidence supporting the suitability of the practice. SFS have been effective and important tools for conservation and reintroduction of avian scavengers. However, negative consequences can result from large aggregations of individual birds, disrupting intraguild processes and promoting density‐dependent decreases in productivity. At the community level, SFS favor the congregation of predators (ie facultative scavengers), increasing predation risk on small‐ and medium‐sized vertebrates in the vicinity of the SFS. These feeding stations might also affect processes of natural selection and even render populations maladapted to their natural environments. We also examine future scenarios for avian scavengers in relation to ecosystem services, to changes in agro‐grazing economies and in land uses, and ultimately to rewilding landscapes where SFS play a controversial role.